Basic Exercise Physiology Clinical and Laboratory Perspectives - Saghiv, Moran S.; Sagiv, Michael S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book reviews the assessment of human performance and the role of different exercise modes both in a laboratory and clinical setting. Details of how to successfully perform basic laboratory procedures for exercise training in health and disease, as well as how to apply non-invasive measurements in exercise physiology are provided. Chapters cover how to appropriately use a range of measures in assessing pulmonary function, anaerobic function and oxygen uptake. Techniques for cardiopulmonary rehabilitation and the mechanisms associated with thermoregulation are also described. Interactive exercises enable readers to easily assimilate key concepts and develop a thorough understanding of the topic. Basic Exercise Physiology provides both trainees and professional healthcare staff interested in exercise physiology with a detailed and practically applicable resource on the topic. .
Introduction to exercise physiology -- Metabolism -- Oxygen uptake and anaerobic performances -- Pulmonary function -- Blood pressure -- cardiovascular function -- AGING -- Skeletal muscles -- Thermoregulation -- Exercise effects on the Immune System -- Exercise in hostile environment -- Epigenetics in exercise -- Exercise equipment -- Appendix 1: measurements in exercise physiology -- Appendix 2: Report formats.
Keywords: Cardiology; Human physiology; Sports medicine; Cardiology; Human Physiology; Sports Medicine